The Combination of Immune Checkpoint Blockade and Angiogenesis Inhibitors in the Treatment of Advanced Non-Small Cell Lung Cancer - Ren, Sijia; Xiong, Xinxin; You, Hua; Shen, Jianfei; Zhou, Penghui (Frontiers in Immunology, 2021)
Immune checkpoint blockade (ICB) has become a standard treatment for non-small cell lung cancer (NSCLC). However, most patients with NSCLC do not benefit from these treatments. Abnormal vasculature is a hallmark of solid tumors and is involved in tumor immune escape. These abnormalities stem from the increase in the expression of pro-angiogenic factors, which is involved in the regulation of the function and migration of immune cells. Anti-angiogenic agents can normalize blood vessels, and thus transforming the tumor microenvironment from immunosuppressive to immune-supportive by increasing the infiltration and activation of immune cells. Therefore, the combination of immunotherapy with anti-angiogenesis is a promising strategy for cancer treatment. Here, we outline the current understanding of the mechanisms of vascular endothelial growth factor/vascular endothelial growth factor receptor (VEGF/VEGFR) signaling in tumor immune escape and progression, and summarize the preclinical studies and current clinical data of the combination of ICB and anti-angiogenic drugs in the treatment of advanced NSCLC.